بەراورد کردنی بەرنامەی فێرکاری باخچەی منداڵانی حکومی و ناحکومی بە پێی ڕادەی بەکارهێنانی بەرنامەی مۆنتێسوری - عبدالله, م. د.فرمان زاهر; قادر, ساوێن عبدالکریم (Sulaimani Journal for Humanities, 2023)
The aims of this study are to compare the curriculum of public and private kindergartens according to: (1) the extent of the use of Montessori program from the perspective of teachers, (2) the extent of the use of speech style dimension, and (3) the extent of the use of sensory development dimension. In this research, descriptive method is used. The research community consists of kindergarten teachers in Sulaimani. The study sample includes 222 public and private kindergarten teachers in Sulaimani. The research tool is the criteria of (Yazdanpana, 2014) for the measurement of the degree of use of the Montessori program. The tool consists of (42) items each of which has (5) choices including (very much, a lot, somewhat, little, very little).It is divided into five dimensions including (speech style, sensory development, cultural dimensions, practical real life, the mathematical ability and environmental science). The most important statistical tools used are Alphacronbach, T-test for one and two independent samples, Kolmogorov-Sminrow equation. Among the most important findings of the study: The extent of use of the Montessori program in general, as well as according to the dimensions of speech and sensory development, varies between public and private kindergartens. In light of these results, several recommendations have been made.
Keywords: Learning programs; Montessori; Government and nongovernment kindergartens